The simplified form of the equation is [tex]\rm -69.19x+38.2[/tex].
Equation; [tex]\rm -9.2(8x - 4) + 0.7(2 + 6.3x)[/tex]
The simplified form of the equation;
To determine the simplified form of the equation following all the steps given below.
Equation; [tex]\rm -9.2(8x - 4) + 0.7(2 + 6.3x)[/tex]
Then,
The simplified form of the equation is,
[tex]\rm =-9.2(8x - 4) + 0.7(2 + 6.3x)\\ \\ = (-9.2) (8x)- (-9.2)(4) + (0.7)(2) + (0.7) (6.3x)\\ \\ =-73.6x -(-36.8) +(1.4)+(4.41x)\\ \\ = -73.6x+36.8+1.4+4.41x\\ \\ =-69.19x+38.2[/tex]
Hence, The simplified form of the equation is [tex]\rm -69.19x+38.2[/tex].
To know more about Equation click the link given below.
https://brainly.com/question/26252222